Survey of activities and stationary sources of air pollution in the city of Balsas-MA (Research, Society and Development, 2021)
This paper presents a diagnosis of air pollution through the quantification and analysis of the characteristics of the main pollutant sources in the region of the city of Balsas-Ma, through the survey of data about the mentioned points. The city of Balsas, located in the southern region of the state of Maranhão, besides already being a region well known for agribusiness and the intensification of agricultural mechanization, is undergoing an increasing process of industrialization. From the commercial point of view, this situation is excellent, but from the sanitary, toxicological, and environmental point of view, this situation, when not done correctly, can cause damage to the population and to the ecosystem of the region. Therefore, this work aims to verify which and how many points of emission of fixed pollutants are located in the region of the city of Balsas, besides performing a characterization of the possible pollutants that are emitted by these points. Thus, this work showed that even in a profile given as moderate, the city has a tendency to have rates that may rise over time, for some reasons, such as: lack of supervision by environmental agencies; and lack of awareness by the population, which ignores all signs that the damage generated by the emission of pollutants affects not only the environment, but all beings living in that environment, and this includes the human being.